Synthesis and characterization of levan hydrogels and their use for resveratrol release - TOKSOY ÖNER, EBRU; GENÇ, SEVAL (SAGE PUBLICATIONS LTD, 2021)
Considering the need for systematic studies on levan based hydrogels to widen their use in drug delivery systems and biomedical applications, this study is mainly focused on the synthesis and comprehensive characterization as well as drug release properties of hydrogels based on Halomonas levan (HL) and its chemical derivatives. For this, hydrolyzed and phosphonated HL derivatives were chemically synthesized and then cross-linked with 1,4-Butanediol diglycidyl ether (BDDE) and the obtained hydrogels were characterized in terms of their swelling, adhesivity, and rheological properties. Both native and phosphonated HL hydrogels retained their rigid gel like structure with increasing shear stress levels and tack test analysis showed superior adhesive properties of the phosphonated HL hydrogels. Moreover, hydrogels were loaded with resveratrol and entrapment and release studies as well as cell culture studies with human keratinocytes were performed. Biocompatible and adhesive features of the hydrogels confirmed their suitability for tissue engineering and drug delivery applications.
Keywords: Halomonas levan; fructan; hydrogels; resveratrol; skin tissue engineering; drug delivery system; HALOMONAS-SMYRNENSIS; MULTILAYER FILMS; SULFATED LEVAN; IN-VITRO; NANOPARTICLES; STABILITY; DELIVERY; PH